Tumor-associated CD163+ macrophage as a predictor of tumor spread through air spaces and with CD25+ lymphocyte as a prognostic factor in resected stage I lung adenocarcinoma. (May 2022) - Yoshida, Chihiro; Kadota, Kyuichi; Yamada, Kaede; Fujimoto, Syusuke; Ibuki, Emi; Ishikawa, Ryo; Haba, Reiji; Yokomise, Hiroyasu
Highlights: CD163 + TAMs are independent predictors of tumor spread through air spaces. High CD25 + /CD163 + immune infiltration predicts worse recurrence-free probability. Multivariate analysis showed that CD25 + /CD163 + is an independent prognostic factor. High CD25 + /CD163 + is associated with several clinical features. Abstract: Objective: Lung cancer can spread in numerous ways, including spread through air spaces (STAS). A high number of CD68 + tumor-associated macrophages (TAMs), which creates a favorable microenvironment for tumor progression, is an independent predictor of increased STAS rate and is used as a pan-macrophage marker, whereas CD163 is used as an M2 macrophage marker. A high number of CD25 + tumor-infiltrating lymphocytes (TILs) is associated with the frequency of STAS. This study investigated the influence of M2 macrophages and CD25 + TILs on STAS and postoperative recurrence in patients with stage I lung adenocarcinoma who underwent curative resection. Methods: We analyzed data from 485 patients with stage 0–I lung adenocarcinoma who underwent resection between 1999 and 2016. Tissue microarrays were constructed, and immunohistochemical analysis was performed for CD3, CD4, CD8, CD45RO, CD25, CD20, CD68, and CD163. Three tumor areas with the highest density of immune cells were photographed, and the immune cells were quantified. Associations between variables were analyzed using chi-square tests and Mann–Whitney U tests. Recurrence-free probability (RFP) was analyzed using log-rank tests and Cox proportional hazards models. Results: CD163 + TAMs were identified as an independent predictor of a higher rate of STAS ( P < 0.001). Analysis of biologically relevant immune cell combinations revealed that patients with high CD25 + TILs and high CD163 + TAMs had a significantly lower RFP (5-year RFP, 74%) than those with other combinations of CD25 and CD163 (5-year RFP, 90%; P < 0.001). Multivariate analysis showed that high CD25 + /high CD163 + immune cell infiltration was an independent predictor of RFP. Conclusion: We demonstrated that a higher density of M2 macrophages is an independent predictor of a higher STAS incidence. A high CD25 + /high CD163 + immune cell infiltration ratio is a significant prognostic factor for stage 0–I lung adenocarcinoma.